Neonatal fatty acid status and cardiometabolic health at 9 years. (September 2016) - Seggers, Jorien; Kikkert, Hedwig K.; de Jong, Corina; Decsi, Tamas; Boehm, Gunther; Hadders-Algra, Mijna
Abstract: Background: Long chain polyunsaturated fatty acid (LCPUFA) status is associated with risk of cardiovascular diseases in adulthood. We previously demonstrated no effect of LCPUFA supplementation after birth on BP and anthropometrics. Little is known about the association between fatty acid status at birth and cardiometabolic health at older ages. Aim: To evaluate associations between docosahexaenoic acid (DHA) and arachidonic acid (AA) levels in the umbilical cord and blood pressure (BP) and anthropometrics at 9 years. Study design: Observational follow-up study. Multivariable analyses were carried out to adjust for potential confounders. Subjects: 229 children who took part in a randomized controlled trial (RCT) on the effects of LCPUFA formula supplementation. Outcome measures: BP was chosen as primary outcome; heart rate and anthropometrics as secondary outcomes. Results: AA levels in the wall of the umbilical vein and artery were negatively associated with diastolic BP (B: vein − 0.831, 95% CI: − 1.578; − 0.083, p = 0.030; artery: − 0.605, 95% CI: − 1.200; − 0.010, p = 0.046). AA was not associated with systolic BP; DHA not with diastolic nor systolic BP. The AA:DHA ratio in the umbilical vein was negatively associated with diastolic BP (B: − 1.738, 95% CI: − 3.141; − 0.335, p = 0.015). Heart rate and anthropometrics were not associated with neonatal LCPUFA status. Conclusions: Higher AA levels and a higher AA:DHA ratio at birth are associated with lower diastolic BP at age 9. This suggests that the effect of LCPUFAs at early age is different from that in adults, where DHA is regarded anti-adipogenic and AA as adipogenic. Highlights: Adequate supply of Long-Chain PolyUnsaturated Fatty Acids (LCPUFA) to the fetus is crucial for fetal programming. Consequently, prenatal LCPUFA status may influence blood pressure and anthropometrics later in life. Higher AA levels in the wall of the umbilical vessels are associated with lower diastolic blood pressure at 9 years. Higher AA:DHA ratios in the wall of the umbilical vessels are associated with lower diastolic blood pressure at 9 years. Our study suggests that high AA levels are associated with better cardiometabolic health in later life. This contrasts with the effects in adults, where high DHA is considered anti-adipogenic.